Capturing the instantaneous flow structure in gas-solid circulating fluidized bed using high-speed imaging and fiber optic sensing. (2nd November 2019) - Wei, Xiaoyang; Zhu, Jesse
Graphical abstract: Do we really know the instantaneous flow structure in gas-solid circulating fluidized bed? Highlights: Clusters have their solids holdup increase sharply and monotonically from the surrounding. Some clusters, known as trough clusters, are surrounded by dispersed particles. Other clusters, known as crest clusters, are immersed in coalesced particles. Abstract: Knowing the instantaneous flow structure in a gas-solid circulating fluidized bed (CFB) is extremely crucial for the understanding of fast fluidization and the development of numerical models. Up to now, numerous studies have been reported on the instantaneous flow structure, but essential information, such as phase classification, solids holdup mapping, macro-scale fluctuation and much more, remains insufficient for a thorough understanding. In this work, the instantaneous flow structure was captured in large-scale CFBs using high-speed imaging and fiber optic sensing. The instantaneous solids holdup mapping across the riser is first computed from images with a verified calibration between solids holdup and grayscale. Based on the solids holdup characteristics, the gas-solid flow in a CFB riser is classified into distinctive phases. Macroscopically, there is a trough phase having continuous low solids holdup and a crest phase having continuous high solids holdup, causing the mean solids holdup across the riser to fluctuate significantly. Within the trough phase, there are trough clusters (particle aggregations) surrounded by dispersed particles (dilute atmosphere). Within the crest phase, there are crest clusters (particle aggregations) surrounded by coalesced particles (dense atmosphere). The above flow structure is further verified with the instantaneous solids holdup obtained using fiber optic sensing in terms of solids holdup characteristics and phase dimensions. Collectively, this study deepens the understanding of fast fluidization, prepares for further phase characterization, and contributes to the development of numerical modeling.